(untitled) (Research, Society and Development, 2024)
Introduction: Bariatric surgery (BS) has proven to be a great ally not only in the treatment of obesity but also of Diabetes Mellitus (DM), due to its various impacts on glucose homeostasis. The most studied surgeries in terms of efficacy and safety are Roux-en-Y Gastric Bypass (RYGB), Sleeve Gastrectomy (SG), Biliopancreatic Diversion (BPD), and Laparoscopic Adjustable Gastric Banding (LAGB). The aim of this study is to evaluate the impacts of different BS techniques on the remission of type 2 diabetes (DM2) and on micro and macrovascular complications. Methodology: This is an integrative review about the impact of BS on DM2. Data from the Virtual Health Library (VHL), Scientific Electronic Library Online (SciELO), and the National Library of Medicine (PubMed) were used, crossing the descriptors "Bariatric Surgery", "Diabetes Mellitus", "Complications", and "Remission", to answer the question formulated through the PICO strategy. Results and Discussion: RYGB and SG stand out in DM2 remission rates, with similar statistics, especially in the long term. The impact on macrovascular complications is positive, especially in the incidence of cardiovascular events. Regarding microvascular complications, the positive impact of BS on diabetic nephropathy stands out, while evidence regarding diabetic retinopathy is still inconclusive. Conclusion: Factors that improve BS outcomes should be taken into account, such as patient age, duration of the disease, and HbA1c levels. Even after remission, continuous nutritional, physical, and glycemic monitoring should be maintained.